Determination of access to medicines for children living on poor households of Peninsular Malaysia - Asmalita Syaiful
A study on access to medicines for children living in poor households (living on RM100 per capita/month) in Peninsular Malaysia was carried out to determine whether these children can access medicines when they get sick. this study also aimed to determine the existing barriers that could limit the access to medicines for children living poor households. A semi- structured interview was conducted with the caregiver to determine the socio-demographical background, access to medicines, knowledge, attitude and practice of the caregiver in obtaining medicines for treatment fever, asthma and epilepsy. the study 132 poor households in Peninsular Malaysia containing of 435 children aged 12 years old and below showed that almost all (99.3%) were fully immunised. The children were described as healthy (89..9%) with 44 had illnesses, mentioned as asthma, febrile convulsion, G6PD deficiency, pneumonia, hypothyroidism and tonsilitis,. In the month before the interview, 76 caregivers reported that their children were unwell. the instances were respiratory tract infection, asthma exacerbation, skin conditions, fever,hypothyroidism, gastritis and a fractured hand. the caregivers obtained medicines for 71/76 (93.4%) of these instances. For the remaining 5 unwell children, the caregivers gave traditional medicines or waited for spontaneous recovery. However one disable caregiver was unable to obtain medicines. Comparing between children living in poor households in Klang Valley (urban area) and East Cost of Peninsular Malaysia (rural area) showed that these was no difference (p<0.05) in access to medicines whereby the children i both regions received medicines when they get sick. There was no significant difference sociodemographically between the two designated area, expert for the mean number of children in each household. Knowledge, attitude and practice among caregiver in obtained medicine for the unwell children were scored as good. Barriers to accessing medicine included cost, distance and disability. The caregiver had good knowledge on febrile illness and asthma but none on epilepsy. However all 132 interviewed caregiver will give medicine for epilepsy on doctor's advise. In conclusion, this study suggest that children in poor households of Malaysia are able to access medicine adequately.